ANALISIS PEMILIHAN ALTERNATIF MATERIAL PADA PEMBANGUNAN BENDUNG (Studi Kasus Pembangunan Bendung Aporo-Sulawesi Tenggara) - Ratnayanti, Rini; Nugraha, Mulya; Yustiana, Fransiska (Jurnal Teknik Sipil ITENAS, 2007)
The high of project cost to built a strong costruction can be minimized by planning optimization. Optimum planning include to plan an optimum structure planning, to choose an appropriate construction technique, construction material selection, etc. the goal of optimum planning is try to gain the lowest project to select economic material construction. It can be done by selecting construction material alternative. The material alternative applied is based on result of material survey which available. Therefore, selected material alternative is concrete and stone-concrete combination. Being have a list of material price, transport fee is added on the price from survey, the next step is analyzing material cost project site. That cost will be mentioned as the material cost in each alternatives of construction item. Material price, labor salary and equipment cos t have strong influence to count the value of a project. In this case, labor salary determined by regional government in that location. Mean while, equipment cost is gotten by analysed by of operational equipment cos per hour. After all data achieved , then analyze unit cost of project according to value per unit of working volume. The result of this analysing shows that project value of concrete dam construction is Rp. 6.036.260.480 and stone-concrete combination dam is Rp. 5.716.901.100. According to both alternatives, the more economical is the choice, that is the working of stone-concrete combination assembly.